2018
DOI: 10.1123/jsm.2017-0296
|View full text |Cite
|
Sign up to set email alerts
|

Performance Leadership and Management in Elite Sport: A Black and White Issue or Different Shades of Grey?

Abstract: In this study, the authors interviewed Olympic athletes about their perceptions of their leaders and managers, with a particular focus on perceptions of negatively valenced and socially undesirable characteristics and their effects. The results highlight five main dark characteristics: self-focused, haughty self-belief, inauthentic, manipulative, and success-obsessed. The findings also indicate negative effects of such characteristics (viz., performance and career threats, affected confidence, pressure and anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Our findings indicate that leadership styles did not tend to vary by industry except for a significant finding amongst hotel managers. The results of this study support the literature in finding that leaders and managers have complex personalities that impact behaviors and performance (Arnold, Fletcher, & Hobson, 2018). There is not an optimal leadership style (Cutler, 2014) and there is not a "one-sizefits-all" personality model for leadership (Parr, Lanza, & Bernthal, 2016).…”
Section: Introductionsupporting
confidence: 78%
“…Our findings indicate that leadership styles did not tend to vary by industry except for a significant finding amongst hotel managers. The results of this study support the literature in finding that leaders and managers have complex personalities that impact behaviors and performance (Arnold, Fletcher, & Hobson, 2018). There is not an optimal leadership style (Cutler, 2014) and there is not a "one-sizefits-all" personality model for leadership (Parr, Lanza, & Bernthal, 2016).…”
Section: Introductionsupporting
confidence: 78%
“…Such behaviours, however, are incompatible with virtue ethics and contradict three decades of research into social learning theory (Bandura, 1986) and leadership ethics (Barling, 2014). That said, Arnold, Fletcher and Hobson (2018) offer support to the idea that there is a positive side to negative and abusive coaching. Based on a qualitative study of 11 former Olympians, the athletes interviewed suggested that negative and abusive coaching behaviours may have a positive effect in supporting the development of resilience and preparing athletes for hostile competitive environments.…”
Section: The Three Es Of Values-based Coaching Ethicalitymentioning
confidence: 87%
“…Based on a qualitative study of 11 former Olympians, the athletes interviewed suggested that negative and abusive coaching behaviours may have a positive effect in supporting the development of resilience and preparing athletes for hostile competitive environments. However, given that these athletes had achieved a successful career (see Arnold et al, 2018), such beliefs are likely to be influenced by survivorship bias.…”
Section: The Three Es Of Values-based Coaching Ethicalitymentioning
confidence: 99%
“…In line with Morgan (2006b), we also found that one source of power was how both NGB-1 and individuals in the sport persuaded others to support them and their interests. Arnold, Fletcher, and Hobson (2018) found that so-called "dark leaders" drew their power from people through manipulation. Our findings supported findings of how both coercive and reward power could be used to create networks of subservient followers.…”
Section: Power Relations As the Key Social Process In A Change Of Culturementioning
confidence: 99%